2017
DOI: 10.1371/journal.pone.0186033
|View full text |Cite
|
Sign up to set email alerts
|

GPR40 partial agonists and AgoPAMs: Differentiating effects on glucose and hormonal secretions in the rodent

Abstract: GPR40 agonists are effective antidiabetic agents believed to lower glucose through direct effects on the beta cell to increase glucose stimulated insulin secretion. However, not all GPR40 agonists are the same. Partial agonists lower glucose through direct effects on the pancreas, whereas GPR40 AgoPAMs may incorporate additional therapeutic effects through increases in insulinotrophic incretins secreted by the gut. Here we describe how GPR40 AgoPAMs stimulate both insulin and incretin secretion in vivo over ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…In DIO-F344 rats given T-3601386 for 4 weeks, significant increases in plasma GLP-1 levels were observed following the single dose of T-3601386 (Fig 3D and 3E) , suggesting the continuous elevation of plasma GLP-1 levels during the repeated dosing study. These results are consistent with a previous report that a GPR40 full agonist exerts BW-lowering effect with the augmentation of circulating GLP-1 [16] .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…In DIO-F344 rats given T-3601386 for 4 weeks, significant increases in plasma GLP-1 levels were observed following the single dose of T-3601386 (Fig 3D and 3E) , suggesting the continuous elevation of plasma GLP-1 levels during the repeated dosing study. These results are consistent with a previous report that a GPR40 full agonist exerts BW-lowering effect with the augmentation of circulating GLP-1 [16] .…”
Section: Resultssupporting
confidence: 94%
“…In the GI tract, GPR40 has been reported to co-localize not only with GLP-1 and GIP but also with other intestinal hormones [44] , and in fact, peptide YY (PYY) secretion was observed after dosing with other full agonists [16, 17] . Previous reports suggested that a novel strategy through dual receptor agonism of GLP-1/GIP or GLP-1/PYY would lead to a greater BW loss with anti-diabetic effects than each mono-hormonal therapy [45, 46] .…”
Section: Discussionmentioning
confidence: 99%
“…Although a further study is essential to elucidate the mechanism by which GPR40 agonism regulates food intake and body weight, this property of SCO-267 may be beneficial in patients who are overweight or obese and have type 2 diabetes. SCO-267 stimulated glucagon secretion in rats, which is consistent with a previous study using a GPR40 full agonist (Pachanski et al, 2017). This suggests that GPR40 full agonists exhibit a direct targeted effect on glucagon secretion.…”
Section: Discussionsupporting
confidence: 91%
“…Recent data are still highly polarized, with some authors supporting ( 255 ), and others disproving this ( 256 ), or even indicating that GPR40 protects β-cells from lipotoxicity ( 257 ) rendering difficult to draw any conclusive mechanistic involvement in healthy and diabetic individuals. Nonetheless, the activation of this receptor with FFAs has demonstrated to induce the secretion of incretins ( 79 , 258 ) glucagon ( 78 , 250 ) and partially glucose-stimulated insulin ( 259 , 260 ) reducing food intake, and lowering body weight in animals models ( 261 ). Mice without a functional GPR40 display an impaired CCK and GLP-1 secretion after an oil gavage, while surprisingly animals deficient for GPR120 display a normal corn oil-induced GLP-1 secretion ( 80 , 262 ).…”
Section: Long and Middle Chain Fatty Acid Receptorsmentioning
confidence: 99%